Defensa de Proyectos de Enfermería - Llivi Ruilova, Danny Vicente (2023)
In compliance with the established planning, the first week of defense of the research projects of the degree modality and incorporation of the new professionals of the Republic of Ecuador of the students of the Nursing career, of the Faculty of Health Sciences, was carried out. and the Human Being of the UEB, which was attended by Mgtr. Silvana López Paredes, Dean; and the members assigned to serve on the tribunals.